Політичні права та свободи людини і громадянина в Україні: поняття, види, характеристика - Федоренко, В.; Fedorenko, V. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Стаття присвячена розкриттю сутності та змісту політичних прав і свобод людини в Україні в конституційних реаліях сьогодення. Саме вони визначають зміст конституційно-правового статусу людини як політично активного громадянина. Свавільні порушення владою громадянських і політичних прав людини, зокрема, права на участь в управлінні державними справами стали визначальною причиною більшості революцій, включаючи Революцію гідності в Україні. Здійснюється характеристика конституційних політичних прав громадян. The author elucidates the nature and content of political rights and freedoms in Ukraine in the terms of constitutional realities oftoday. It is emphasized that political rights and freedoms of citizens, alongside with their personal rights, were determined as the most important long ago, in the period of bourgeois-democratic revolutions in Europe and the wars of independence in America in the XVIII-XIX centuries. They determine the content of the constitutional and legal status of a person as a politically active citizen. Arbitrary abuse of civil and political rights by the authorities, including the right to participate in public affairs, has caused most of the revolutions, including the Revolution of dignity in Ukraine. The article presents detailed characterization of political rights assigned in the Constitution of Ukraine: the freedom of membership in political parties and public organizations (art. 36); the rights to participate in state management, in national and local referendums, to elect freely and be elected to the state and local government bodies (Part. 1, Art. 38); equal access to the state service and service in local government bodies (p. 2, Art. 38); for peaceful meetings (art. 39), the individual or collective petitions, or personal appeal to the state authorities, local authorities (Art. 40) and others.
Political Rights and Freedoms of a Man and a Citizen in Ukraine: Concepts, Types and Characteristics
Keywords: права та свободи людини; політичні права і свободи людини і громадянина; політична участь громадян; право на участь в управлінні державними справами; право на участь у виборах і референдумі; право на участь у мирних заходах; право на участь у політичних партіях; political rights and freedoms of man and citizen; the right to participate in state management; the right to participate in elections and referendum; the right to participate in peaceful activities; the right to participate in political parties